Mutação constitucional como meio difuso de efetivação dos direitos e garantias fundamentais - Silva, Roberto Carlos Rocha da (2014)
The present work comprises a study on the phenomenon of Constitutional Mutation On the basis, in particular, of a number of cases involving fundamental rights and guarantees Occurred after the Promulgation of the Federal Constitution of 1988. In order to achieve this Objective, extensive doctrinal research was used, one of which was based on authors Renowned not only national but also international, such as Paulo Bonavides, George Marmelstein, Otto Bachof, Konrad Hesse, Hans Kelsen, Friedrich Müller, etc. Against It is necessary to examine questions concerning methods of interpreting the Constitution, as well as As situations specifically aimed at an informal computing of the political-normative text From the Magna Carta Brasileira. Focusing the work on these points, we also analyzed the Different types of constitutional mutations (including those considered unconstitutional) Aimed at national doctrine. To do so, use as a comparative parameter to Jurisprudence of the Federal Supreme Court. Finally, we sought to discuss the importance of Of judicial activism in safeguarding the fundamental rights and guarantees of the individual.